2014
DOI: 10.1158/0008-5472.can-13-2893-t
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Oxidative Metabolism in Melanoma Causes Metabolic Compensation through Glucose and Glutamine Utilization

Abstract: Metabolic targets offer attractive opportunities for cancer therapy. However, their targeting may activate alternative metabolic pathways that can still support tumor growth. A subset of human melanomas relies on PGC1a-dependent mitochondrial oxidative metabolism to maintain growth and survival. Herein, we show that loss of viability caused by suppression of PGC1a in these melanomas is rescued by induction of glycolysis. Suppression of PGC1a elevates reactive oxygen species levels decreasing hypoxia-inducible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 38 publications
1
77
0
Order By: Relevance
“…While the PGC coactivators (consisting of PGC-1α, PGC-1β, and PRC) exhibit some degree of redundancy, PGC-1α knockout mice exhibit multi-tissue defects in mitochondrial metabolism indicating unique functions for PGC-1α that cannot be compensated for by the other family members (Leone et al, 2005; Lin et al, 2004). A growing body of evidence points toward an important role for PGC-1α in cancer, however an important dichotomy exists, with reports of pro and anti-tumorigenic effects of PGC-1α expression in different cancer types (D'Errico et al, 2011; Haq et al, 2013; LeBleu et al, 2014; Lim et al, 2014; Vazquez et al, 2013; Yan et al, 2014). A better understanding of the role of PGC-1α in different tumor types and at different stages of tumorigenesis will be important in determining whether this pathway will be amenable to therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…While the PGC coactivators (consisting of PGC-1α, PGC-1β, and PRC) exhibit some degree of redundancy, PGC-1α knockout mice exhibit multi-tissue defects in mitochondrial metabolism indicating unique functions for PGC-1α that cannot be compensated for by the other family members (Leone et al, 2005; Lin et al, 2004). A growing body of evidence points toward an important role for PGC-1α in cancer, however an important dichotomy exists, with reports of pro and anti-tumorigenic effects of PGC-1α expression in different cancer types (D'Errico et al, 2011; Haq et al, 2013; LeBleu et al, 2014; Lim et al, 2014; Vazquez et al, 2013; Yan et al, 2014). A better understanding of the role of PGC-1α in different tumor types and at different stages of tumorigenesis will be important in determining whether this pathway will be amenable to therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also indicated that robust mitochondria respiration activity strongly relied on autophagy and FAO, which provide nutrients to mitochondria (79). Suppression of the compensatory fluxes could greatly increase the sensitivity of melanoma cells to OxPhos inhibition (79,105). These data highlight the metabolic flexibility of cancer and emphasize the demand for a multitargeted therapeutic strategy to reduce or avert the treatment resistance.…”
Section: Therapeutic Implicationsmentioning
confidence: 89%
“…However, these treatments simultaneously activate alternate metabolic fluxes in a small set of cancer cells (104). The increased ROS production caused by PGC1a inhibition stabilizes HIF1a protein, and HIF1a induces a metabolic switch from OxPhos to glycolysis which promotes cell survival (105). Surprisingly, even a combinatory suppression of PGC1a and HIF1a could not eradicate tumors in mice.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Likewise, high expression of PGC1a in melanoma cells causes an increase in oxidative energy metabolism, increased expression of ROS-detoxifying enzymes, and resistance to ROS-inducing drugs (39). Upon PGC1a inhibition, such OXPHOS-dependent melanoma cells reverted to a glycolytic energy metabolism (40).…”
Section: Discussionmentioning
confidence: 99%